Hak Atas Pembangunan Sebagai Hak Asasi Manusia - Marzuki, Suparman (Unisia, 2016)
The increasing of an unequal realities based on the equality as asserted in the Universal Declaration of Human Rights is as result of development. Because the development in the states of third world (developing countries) which depended on market mechanism with its variety emerged many problems. It seems development did not depart from the human rights perspective. It did not only raise the impact including on poor society, but also emerged crisis in economic, politic, law and cultural, and crisis in all fields mentioned above influences on human life largely. In this sense, according to the writer to maintain human rights there is also human obligations. In the context of fulfilling the development rights the government and the people have human obligations to fill sphere of social, economic and cultural so the rights in development could be enjoyed by all without exception.